The Use of Imagery and Its Significance in Literary Studies - Sharma Paudyal , Homa Nath (The Outlook: Journal of English Studies, 2023)
Imagery is one of the various techniques that poets and other writers consciously or unconsciously use to make their expressions more powerful. It is, therefore, imperative for readers to have adequate knowledge about this literary technique, but most readers fail to seriously notice the application of imagery and to describe how it assists in the effective literary analysis and pedagogical process. Particularly used in poetry, ‘imagery’ has its great importance as it helps readers activate their’ sense organs and perceive the message as intended by poets or other writers. The main issue that encouraged this study is to explore the reasons behind the application of imagery and the extent of contribution it can make to literary analysis and pedagogy. The objective of the study is to explain the significance of imagery in the literary analysis and pedagogical process. Various print as well as online materials have been consulted to gather references in the article. Thus qualitative research method based on secondary sources has been applied to substantiate the argument. The findings of the study suggest that the use of imagery makes any text formally artistic and functionally appealing. The study also concludes that the use of imagery in literary texts enhances readers’ perception power as it motivates them by arousing their interest and activating their sense organs.